Numerical ship hydrodynamics an assessment of the Gothenburg 2010 Workshop - Larsson, Lars; Stern, Frederick; Visonneau, Michel (Springer, 2014)
Analysis is made of errors for global (resistance, sinkage and trim and self-propulsion) and local flow (wave elevations and mean velocities and turbulence) variables, including standard deviations for global variables and propeller modeling for self-propulsion